2017
DOI: 10.1002/lno.10595
|View full text |Cite
|
Sign up to set email alerts
|

Influence of invasive quagga mussels, phosphorus loads, and climate on spatial and temporal patterns of productivity in Lake Michigan: A biophysical modeling study

Abstract: We applied a three‐dimensional biophysical model to Lake Michigan for the years 2000, 2005, and 2010 to consider the mechanisms controlling spatial and temporal patterns of phytoplankton abundance (chlorophyll a) and lake‐wide productivity. Model skill was assessed by comparison to satellite‐derived Chl a and field‐measured water quality variables. We evaluated model sensitivity to scenarios of varying mussel filter feeding intensity, tributary phosphorus loads, and warm vs. cool winter‐spring climate scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 64 publications
(134 reference statements)
8
93
0
Order By: Relevance
“…Similar to the findings of Warner and Lesht (2015) and Rowe et al (2017), the mechanism underlying this increase in the range of chlorophyll concentrations varied by season. Similar to the findings of Warner and Lesht (2015) and Rowe et al (2017), the mechanism underlying this increase in the range of chlorophyll concentrations varied by season.…”
Section: Nutrient Abatement Programmes and Invasive Filter Feeders Hasupporting
confidence: 77%
See 2 more Smart Citations
“…Similar to the findings of Warner and Lesht (2015) and Rowe et al (2017), the mechanism underlying this increase in the range of chlorophyll concentrations varied by season. Similar to the findings of Warner and Lesht (2015) and Rowe et al (2017), the mechanism underlying this increase in the range of chlorophyll concentrations varied by season.…”
Section: Nutrient Abatement Programmes and Invasive Filter Feeders Hasupporting
confidence: 77%
“…Nutrient abatement programmes intended to limit excessive anthropogenic nutrient loading to aquatic systems from both point-and non-point-sources have generally proven effective and have resulted in improved water quality as indicated by reduced nutrient concentrations and algal biomass (Guildford and Hecky, 2000;Smith, 2006). Rowe et al 2017) the spatial details of an ecosystem's response to reductions in nutrient loading can be difficult to predict and thus complicate efforts to verify the success of nutrient reduction programmes by monitoring. Rowe et al 2017) the spatial details of an ecosystem's response to reductions in nutrient loading can be difficult to predict and thus complicate efforts to verify the success of nutrient reduction programmes by monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate how vertical mixing, stratification, and mussel grazing influence the dynamics of food availability to mussels at littoral vs. profundal habitats in 2015 and to estimate the relative food availability throughout the water column in 2016, we ran simulations using a 1‐dimensional (vertical column) version of the biophysical model described by Rowe et al (). Rowe et al ( a ) showed that 1‐dimensional biophysical model simulations can reproduce seasonal patterns of phytoplankton abundance observed in the Great Lakes, including the spring bloom during the late isothermal and early stratification periods, the deep chlorophyll maximum during stratification, and secondary maxima in surface and bottom chlorophyll associated with fall turnover.…”
Section: Methodsmentioning
confidence: 99%
“…[1980] and Nicklisch et al [2007]. Also, the light attenuation functions are adjusted to 434 Rowe et al (2017). 435…”
Section: Hydrodynamic Model 391mentioning
confidence: 99%